HUBUNGAN ANTARA PENGETAHUAN DENGAN SIKAP PERAWAT DALAM PEMENUHAN KEBUTUHAN SPIRITUAL PASIEN DI BRSUD SUKOHARJO - Yuni Wulan Utami; Supratman Supratman (Jurnal Berita Ilmu Keperawatan, 2009)
Nurses must consent with spiritual aspect in caring of patient beside biology, psychology, social, and cultural aspect, because spiritual aspect have relationship with health and wellness of patient. An aim of this research was analyzing the relationship know ledge attitude to fulfill the patients’s spiritual need. This research was quantitative research and non experimental with descriptive correlation. Research analysis was using product moment correlation. This research is held at November, 7th 2005 until December, 3rd 2005 with 98 respondent. Know ledge variable was measured by the questionnaire use Guttmann scale, while attitude variable was measured by the questionnaire use Likert scale. Result of this research show that most of respondents have adequate know ledge grade and attitude. Good know ledge (37,76%), middle (62,24%) and less (0%). While good attitude (23,47%), middle (76,53%) and less (0%). Result of correlation was r test =0,527 with p value 0,05, so it shows that there is significant relationship between nurses know ledge and attitude to fulfill the patients spiritual need in BRSUD Sukoharjo.